2023
DOI: 10.47974/cjsim-2022-0074
|View full text |Cite
|
Sign up to set email alerts
|

The association between Mendeley early readership and later citations in library and information science journals

Abstract: Altmetrics indicators are useful for assessing the impact of research and have been increasingly used alongside traditional citations in recent years. Mendeley provides readership statistics which give an early indicator of the impact of research outputs. This study aimed to investigate how Mendeley early readership indicator was associated with later citations across nine selected library and information science (LIS) journals. This study examined bibliographic data of 9 LIS journals extracted from the Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Concerning the association between the classic metrics and altmetrics, the study reported that Dimensions citations were weakly positively correlated with altmetric attention scores. The positive associations were flagged by many other studies also (Costas et al, 2015;Parabhoi et al, 2023;Zhao and Wolfram, 2015). So, it can be justified that altmetrics can be used along with classic metrics for measuring the social impact of the LIS research.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Concerning the association between the classic metrics and altmetrics, the study reported that Dimensions citations were weakly positively correlated with altmetric attention scores. The positive associations were flagged by many other studies also (Costas et al, 2015;Parabhoi et al, 2023;Zhao and Wolfram, 2015). So, it can be justified that altmetrics can be used along with classic metrics for measuring the social impact of the LIS research.…”
Section: Findings and Discussionmentioning
confidence: 99%